Prior Consultation without Social Accountability: An Analysis of the Colombian Mining Policy (2010-2014) - Zúñiga Delgado, Jesús A.; Fiesco Rivas, Leslie M.; Rodrigues de Caires, Carlos M. (Journal Studies of Public Policy, 2024)
Prior consultation is a social accountability tool enabling indigenous and rural communities to engage in decision-making on extractive projects and those with significant environmental impacts. Despite its broad legal recognition in Latin America, its implementation has faced considerable obstacles. This article defines a causal mechanism to explain the persistent deficits in social accountability within Colombia’s mining sector, a pioneer in regulating the right to prior consultation. Using Bayesian process tracing, the study shows that, following the adoption of prior consultation, private interests influenced the public agenda, weakening social accountability through the implementation of an extractive mining development model, sectoral reforms favoring private investment, and the centralization of mining governance. The analysis reveals the inadequacy of formal institutionalization of participation mechanisms and underscores the critical role of policy design processes in the discursive, strategic, and operational consolidation of these institutional innovations.